The Effect of The Development of Korean Drama on Indonesia Used As Cultural Diplomacy in 2019-2021 - Febriana, Hanindya Ratih; Lubis, Flori Mardiani; Gustianti, Nurbani Adine (Mandala: Jurnal Ilmu Hubungan Internasional, 2023)
The spread of South Korean culture in Indonesia looks quite significant because it attracts many Indonesian people and makes them fans of the reach of Korean culture. This phenomenon did not occur by chance but was managed well by the South Korean government to use this time as diplomacy through its culture with the target country, namely Indonesia. Koreanization in screen culture in the form of cinema, television, internet, and social media has succeeded in bringing Korean popular culture into Indonesia and getting a positive response from the Indonesian people. With the development of the mass media industry, especially television, this research's background. In this regard, the South Korean government used this opportunity to introduce its country through the mass media and improve its image in other countries. As we also know that nowadays, women are more interested in Korean TV dramas than men. Therefore, with the development of the theme of Korean dramas, Indonesian people are increasingly interested in watching new dramas, making the South Korean government take advantage of this to develop South Korean culture and practice. Keywords; cultural diplomacy, k-drama, Korean popular culture, South Korea, Indonesia